Femtosecond Assisted Deep Lamellar Keratoplasty in a 4½ Year Old Child for Traumatic and Infectious Corneal scar- A Case Report - Amir Pirouzian (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2015)
Purpose: To report a case of central deep corneal scar secondary to trauma and subsequently resolved fungal infection in a 4½ year old and secondary amblyopia treated with femtosecond-assisted deep lamellar keratoplasty (FALK). Methods: A 4½ year old male patient with reduced vision and photophobia as a result of a centrally dense mid-stromal corneal scar in the right eye was referred to Gavin Herbert Eye Institute, University of California, Irvine, by an out of state ophthalmologist for consideration of femtosecondassisted laser lamellar keratoplasty. Following a complete ocular examination, FALK was performed under general anesthesia. Results: The original non-perforating cornea trauma had occurred 10-months previously while the child had accidentally run into a branch of a tree, penetrating the right central cornea and resulting in Aspergillus corneal infection. The penetrating cornea injury was repaired and the ensuing infection was treated with a course of topical antifungal medications. After resolution of the infection, a deep and dense mid-stromal scar, obstructing visual axis, had developed. Irregular astigmatism and secondary amblyopia were present. The zigzag pattern FALK using IntralaseTM laser (AMO, Santa Ana, CA) for both donor and recipient cuts was performed. Conclusions: This is the first case report of traumatic central corneal scar from trauma and infection resulting in amblyopia, which was successfully treated with zigzag-shaped femtosecond assisted laser lamellar keratoplasty in a young child.